2019
DOI: 10.1111/srt.12679
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related biophysical changes of the epidermal and dermal skin in Korean women

Abstract: Introduction The clinical characteristics of skin were investigated to study the inter‐relationship and changes in the biophysical properties of the epidermal and dermal layers associated with aging using noninvasive methods. Methods Our study included 100 healthy women aged between the early 20s and late 60s. Biophysical characteristics of skin such as color (brightness and spots), transparency, wrinkle on crow's feet, elasticity, hydration, sebum content, glossiness, and transepidermal water loss measured un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 25 publications
6
36
3
Order By: Relevance
“…Many people believe that the skin moisture content diminishes with age, and some researchers supported this opinion. 5,16,30 In our study, this phenomenon was observed only for the cheek, but not for the forehead and forearm which presented curves with the peak at around the age of 35 and 40 years old, respectively ( Figure 1A,B,D). Hydration was largely stable for the chin, with even a small increasing trend with age ( Figure 1C).…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Many people believe that the skin moisture content diminishes with age, and some researchers supported this opinion. 5,16,30 In our study, this phenomenon was observed only for the cheek, but not for the forehead and forearm which presented curves with the peak at around the age of 35 and 40 years old, respectively ( Figure 1A,B,D). Hydration was largely stable for the chin, with even a small increasing trend with age ( Figure 1C).…”
Section: Discussioncontrasting
confidence: 47%
“…Nevertheless, a few publications presented a non-monotonic relationship between some parameters and age. 5,9 Instead of the linear regression model, we chose the generalized additive model to fit the change trend of skin parameters with age. The generalized additive model takes the additive form of nonparametric function to get better model interpretation and prediction in non-linear regression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flament et al reported that skin pigmentation was observed with age in Caucasians. In addition, Cho et al researched the age‐related skin color changes in the epidermal and dermal skin in Koreans and discovered that skin transparency and brown spots showed a rapid change at the ages of the early 30s and late 50s.…”
Section: Discussionmentioning
confidence: 99%